Compound C induces protective autophagy in human cholangiocarcinoma cells via Akt/mTOR‐independent pathway. Issue 7 (25th March 2018) - Zhao, Xiaofang; Luo, Guosong; Cheng, Ying; Yu, Wenjing; Chen, Run; Xiao, Bin; Xiang, Yuancai; Feng, Chunhong; Fu, Wenguang; Duan, Chunyan; Yao, Fuli; Xia, Xianming; et al.
Abstract: Compound C, a well‐known inhibitor of AMP‐activated protein kinase (AMPK), has been reported to exert antitumor activities in some types of cells. Whether compound C can exert antitumor effects in human cholangiocarcinoma (CCA) remains unknown. Here, we demonstrated that compound C is a potent inducer of cell death and autophagy in human CCA cells. Autophagy inhibitors increased the cytotoxicity of compound C towards human CCA cells, as confirmed by increased LDH release, and PARP cleavage. It is notable that compound C treatment increased phosphorylated Akt, sustained high levels of phosphorylated p70S6K, and decreased mTOR regulated p‐ULK1 (ser757). Based on the data that blocking PI3K/Akt or mTOR had no apparent influence on autophagic response, we suggest that compound C induces autophagy independent of Akt/mTOR signaling in human CCA cells. Further study demonstrated that compound C inhibited the phosphorylation of JNK and its target c‐Jun. Blocking JNK by SP600125 or siRNA suppressed autophagy induction upon compound C treatment. Moreover, compound C induced p38 MAPK activation, and its inhibition promoted autophagy induction via JNK activation. In addition, compound C induced p53 expression, and its inhibition attenuated compound C‐induced autophagic response. Thus, compound C triggers autophagy, at least in part, via the JNK and p53 pathways in human CCA cells. In conclusion, suppresses autophagy could increase compound C sensitivity in human CCA. Abstract : Our present work reveals that compound C induces protective autophagy in human CCA cells via p53 induction and the JNK pathway.